2011
DOI: 10.1063/1.3666029
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous transport and thermal properties of NiTi and with Cu and Fe-doped shape memory alloys near the martensitic transition

Abstract: The temperature dependent electrical and thermal properties including electrical resistivity (q), specific heat (C P), Seebeck coefficient (S) and thermal conductivity (j) have been studied for the polycrystalline NiTi, Ti 50 Ni 40 Cu 10 and Ti 50 Ni 48.5 Fe 1.5 shape memory alloys from 10-400 K. It was found that the electrical resistivity and Seebeck coefficient exhibit a typical metallic behavior throughout the temperature range investigated. A significant thermal hysteresis between warming and cooling was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 30 publications
0
21
2
Order By: Relevance
“…20 Recently, we investigated electrical and thermal transport studies on 10% Cu and 1.5% Fe substituted TiNi alloys. 22 In this study, a clear thermal hysteresis behavior between warming and cooling condition of resistivity, Seebeck coefficient, and thermal conductivity measurements was observed in the undoped and doped TiNi alloys, which indicated first order martensitic phase transition and also found to be twostage transformation. The anomalous features in the measured physical properties suggested that the modifications in the Fermi surface and strong electron-phonon interaction may play important roles at the martensitic transitions of the TiNi-based alloys.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…20 Recently, we investigated electrical and thermal transport studies on 10% Cu and 1.5% Fe substituted TiNi alloys. 22 In this study, a clear thermal hysteresis behavior between warming and cooling condition of resistivity, Seebeck coefficient, and thermal conductivity measurements was observed in the undoped and doped TiNi alloys, which indicated first order martensitic phase transition and also found to be twostage transformation. The anomalous features in the measured physical properties suggested that the modifications in the Fermi surface and strong electron-phonon interaction may play important roles at the martensitic transitions of the TiNi-based alloys.…”
Section: Introductionmentioning
confidence: 87%
“…However, the value of residual resistivity of the parent TiNi alloy is considerably lower than that of previously reported value, 5 suggesting the highly ordered nature of the sample. Moreover, upon cooling from 400 K, the resistivity shows a sharp rise followed by a sudden fall in the form of two well-defined peaks in the parent TiNi alloy, 22 as seen in the inset of Fig. 1(a).…”
Section: A Electrical Resistivitymentioning
confidence: 93%
See 2 more Smart Citations
“…Such a change in slope was also found in nonmagnetic Ni 50 Ti 50 alloy and was attributed to phonon drag contribution that was broadened by disorder. 32 However, this feature was not observed in the ferromagnetic shape memory alloy Ni 50 Mn 34 In 16 . 22 Upon heating from 10 K, α(T) exhibits hysteresis at T M as is the case with the resistivity, due to the first-order structural phase transition.…”
Section: Resultsmentioning
confidence: 90%